Radikalisme Timur-Tengah dan Pengaruhnya di Indonesia - Darman, Andrianus; Metodius, Fabrizio Olie Valdo; Sitohang, Leopoldus Giovani; Letsoin, Yetva Softiming; Blareq, Yoseph Koverino Gedu (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
In this search, our focus is on Middle-Eastern radicalism and its impact on the Indonesian nation. It seems that radicalism in the Middle East arises from its own historical, political and cultural context. Therefore, it is very peculiar to apply it in this country, since Indonesia has its own particular historical, political and cultural context. However, it is inevitable that the notion of radicalism has entered Indonesia through certain groups, individuals, social media, or networks affiliated with radicalist networks in the Middle East. This fact needs to be addressed by establishing a deradicalization institution and by preserving the treasures of the arts, culture and ethics of the country, Nusantara.